2021
DOI: 10.1158/1541-7786.mcr-20-0633
|View full text |Cite
|
Sign up to set email alerts
|

Mutant KRAS Downregulates the Receptor for Leukemia Inhibitory Factor (LIF) to Enhance a Signature of Glycolysis in Pancreatic Cancer and Lung Cancer

Abstract: Pancreatic cancer is characterized by aberrant activity of oncogenic KRAS, which is mutated in 90% of pancreatic adenocarcinomas. Because KRAS itself is a challenging therapeutic target, we focused on understanding key signaling pathways driven by KRAS as a way to reveal dependencies that are amenable to therapeutic intervention. Analyses in primary human pancreatic cancers and model systems revealed that the receptor for the cytokine leukemia inhibitory factor (LIF) is downregulated by mutant KRAS. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
1
12
1
Order By: Relevance
“…However, Ras-transformation and STAT3 signaling are found to be mutually exclusive in pancreatic cancers, in which KRAS mutation occurs at a 90% frequency ( 90 ). Analyses of primary human pancreatic adenocarcinomas and pancreatic cancer cellular systems showed that the LIF receptor is significantly downregulated in cancers with mutated KRAS, and this downregulation of LIFR was necessary for KRAS-mediated neoplastic transformation.…”
Section: Mitochondrial Function Of Ps-stat3mentioning
confidence: 99%
“…However, Ras-transformation and STAT3 signaling are found to be mutually exclusive in pancreatic cancers, in which KRAS mutation occurs at a 90% frequency ( 90 ). Analyses of primary human pancreatic adenocarcinomas and pancreatic cancer cellular systems showed that the LIF receptor is significantly downregulated in cancers with mutated KRAS, and this downregulation of LIFR was necessary for KRAS-mediated neoplastic transformation.…”
Section: Mitochondrial Function Of Ps-stat3mentioning
confidence: 99%
“…Increased serum LIF is a biomarker to predict lymph node metastasis and distant metastasis in pancreatic cancer patients [43]. Another study, however, showed that expression of LIFR was associated with longer overall survival of pancreatic cancer patients [44]. Oncogenic KRAS downregulates LIFR.…”
Section: Cancer-associated Fibroblast Subtypes and Paracrine Factorsmentioning
confidence: 99%
“…Oncogenic KRAS downregulates LIFR. Downregulation of LIFR is important for KRAS-mediated neoplastic transformation [44]. Wang et al showed that oncogenic KRAS induced LIF expression in pancreatic cancer cells, where the mitogen-activated protein kinase kinase (MEK)/extracellular signal-regulated kinase (ERK) signaling is essential [45].…”
Section: Cancer-associated Fibroblast Subtypes and Paracrine Factorsmentioning
confidence: 99%
“…KRAS is an important oncogene in various cancers; mutant KRAS induces an increase in the expression of GLUT1, glycolysis, and mitochondrial respiration [ 68 ]. As a cellular energy sensor and modulator, AMP-activated protein kinase (AMPK) behavior in tumorigenesis remains largely unsolved.…”
Section: Glucose Metabolismmentioning
confidence: 99%